2006
DOI: 10.1093/ptj/86.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Bone Biology and the Clinical Implications for Osteoporosis

Abstract: Bone biology is a complex and vastly growing area of study. It brings together the traditional fields of anatomy, physiology, and biomechanics with the increasingly complex fields of developmental biology and molecular genetics. For clinicians who treat bone disorders such as osteoporosis, developing a working knowledge of this topic is essential. This article discusses bone from a structural, anatomical, and functional perspective. It reviews skeletogenesis as a developmental process and from a regulatory per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
3
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(149 citation statements)
references
References 30 publications
4
128
3
9
Order By: Relevance
“…No presente estudo a região da crista óssea foi mais atingida devido ao maior teor de tecido ósseo esponjoso, o qual, geralmente, apresenta taxa metabólica maior, respondendo mais rapidamente às mudanças mecânicas do que o osso cortical (Downey & Siegel, 2006). Na análise histomorfométrica notou-se diminuição significativa do POA da mandíbula e do POT do fêmur nos animais tratados com glicocorticóide, evidenciando a redução óssea alveolar mandibular e femural encontrada por outros autores (Fujita et al, 2008;Mahl & Fontanella, 2008;Pinto et al, 2006;Natsui et al, 2006).…”
Section: Resultsunclassified
“…No presente estudo a região da crista óssea foi mais atingida devido ao maior teor de tecido ósseo esponjoso, o qual, geralmente, apresenta taxa metabólica maior, respondendo mais rapidamente às mudanças mecânicas do que o osso cortical (Downey & Siegel, 2006). Na análise histomorfométrica notou-se diminuição significativa do POA da mandíbula e do POT do fêmur nos animais tratados com glicocorticóide, evidenciando a redução óssea alveolar mandibular e femural encontrada por outros autores (Fujita et al, 2008;Mahl & Fontanella, 2008;Pinto et al, 2006;Natsui et al, 2006).…”
Section: Resultsunclassified
“…Dual X-ray absorptiometric (DXA) measurements of areal BMD (g/cm 2 ) at the lumbar spine L1-L4) and the femoral neck were carried out using a Lunar DPX Prodigy densitometer (Lunar, Madison, WI, USA). Daily standardized measurement of a Lunar phantom and Hologic Anatomic spine phantom served as a quality control for the bone densitometer.…”
Section: Bmd Measurementsmentioning
confidence: 99%
“…The bone remodeling unit is composed of osteoblasts, which form bone, and osteoclasts, which break down bone [2]. The osteoblast and osteoclast differentiation and activation depend on a family of biologically related TNF/TNF-like proteins: osteoprotegerin (OPG), receptor activator of nuclear factor (NF) κB (RANK), and RANK ligand (RANKL).…”
Section: Introductionmentioning
confidence: 99%
“…Bone lining cells are rooted from mesenchymal stem cells or osteoprogenitor cells, which is an inactive form of osteoblasts known as "resting osteoblasts". A study reported that bone lining cells might be an osteoblast precursor that regulates crystal growth of bone mineral or a barrier between extracellular fluid and bone (Downey 2006, Datta 2008, Lorenzo 2008, Bonewald 2011.…”
Section: Introductionmentioning
confidence: 99%